Eudendrium arbuscula Wright 1859 - Calder, Dale R. (Zenodo, 2012)
Eudendrium arbuscula Wright, 1859 Figs. 3, 4 Eudendrium arbuscula Wright, 1859: 113, pl. 9, figs. 5, 6.— Segerstedt, 1889: 9, 24.— Rees & Rowe, 1969: 11.— Jägerskiöld, 1971: 62.— Marques et al ., 2000: 81, fig. 15 [the specific name arbuscula Wright, 1859 conserved and placed on the Official List of Specific Names in Zoology, Opinion 1956 (ICZN 2000)]. Eudendrium wrighti .— Jäderholm, 1909: 51 [incorrect subsequent spelling] [ Eudendrium wrightii Hartlaub, 1905 placed on the Official Index of Rejected and Invalid Names in Zoology, Opinion 1956 (ICZN 2000)]. Type locality. UK: Scotland, Firth of Forth, Queensferry (Wright 1859: 113). Museum material. Kosterhavet, 58°53.585’N, 11°06.239’E, 14– 10 m, 06.ix.2010, biological dredge, R / V Nereus , four colony fragments, up to 3.1 cm high, without gonophores, ROMIZ B3880. Remarks. Colonies examined here were quite small and lacked gonophores, but they corresponded with Eudendrium arbuscula Wright, 1859 as described by Schuchert (2008b). The largest colony had a polysiphonic stem basally that lacked a bark-like covering as in the similar E. annulatum Norman, 1864; hydranths were small and bore a basal band of large microbasic euryteles having a straight shaft. The specific name arbuscula Wright, 1859, as published in the binomen Eudendrium arbuscula , was conserved and placed on the Official List of Specific Names in Zoology (ICZN Opinion 1956). It had been threatened by a senior secondary homonym, arbuscula (d’Orbigny, 1846), as published in the binomen Tubularia arbuscula , a name placed in the same Opinion on the Official Index of Rejected and Invalid Specific Names in Zoology. Also placed on the Official Index in that Opinion was the name E. wrightii Hartlaub, 1905, a replacement name for E. arbuscula Wright. As noted by a number of authors (e.g., Marques & Vervoort 1999; Schuchert 2008b), the specific name is a noun in apposition and correctly spelled as “ arbuscula ,” not “ arbusculum .” Eudendrium arbuscula , a relatively shallow water species, has been reported several times from the west coast of Sweden (see Checklist), from Denmark (Kramp 1935b; Schuchert 2008b), and from the Oslofjord, Norway (Christiansen 1972). Reported distribution. West coast of Sweden.—Bohuslän (Marques et al . 2000) to Malösund (Jäderholm 1909, as E. wrighti ). Elsewhere.—North Atlantic: Norway to Brittany (Schuchert 2008b); northern Canada (Calder 1972). : Published as part of Calder, Dale R., 2012, On a collection of hydroids (Cnidaria, Hydrozoa, Hydroidolina) from the west coast of Sweden, with a checklist of species from the region 3171, pp. 1-77 in Zootaxa 3171 (1) on pages 6-8, DOI: 10.11646/zootaxa.3171.1.1, http://zenodo.org/record/5247704 : {"references": ["Wright, T. S. (1859) Observations on British zoophytes. Edinburgh New Philosophical Journal, new series, 10, 105 - 114.", "Segerstedt, M. (1889) Bidrag till kannedomen om hydroid-faunan vid Sveriges vestkust. Bihang till Kongliga Svenska Vetenskaps-Akademiens Handlingar, 14, Afdelning 4, 4, 1 - 28.", "Rees, W. J. & Rowe, M. (1969) Hydroids of the Swedish west coast. Acta Regiae Societatis Scientiarum et Litterarum Gothobergensis, Zoologica, 3: 1 - 23.", "Jagerskiold, L. A. (1971) A survey of the marine benthonic macro-fauna along the Swedish west coast 1921 - 1938. Acta Regiae Societatis Scientiarum et Litterarum Gothobergensis, Zoologica, 6, 1 - 146.", "Marques, A. C., Mergner, H., Hoinghaus, R., Santos, C. M. D., & Vervoort, W. (2000) Morphological study and taxonomical notes on Eudendriidae (Cnidaria: Hydrozoa: Athecatae / Anthomedusae). Zoologische Mededelingen, 74, 75 - 118.", "Jaderholm, E. (1909) Northern and Arctic invertebrates in the collection of the Swedish State Museum (Riksmuseum). IV. Hydroiden. Kungliga Svenska Vetenskapsakademiens Handlingar, ny foljd, 45 (1), 1 - 124.", "Hartlaub, C. (1905) Die Hydroiden der magalhaensischen Region und chilenischen Kuste. Zoologische Jahrbucher, Supplement-Band 6, Fauna Chilensis, 3, 497 - 714.", "Schuchert, P. (2008 b) The European athecate hydroids and their medusae (Hydrozoa, Cnidaria): Filifera Part 4. Revue Suisse de Zoologie, 115, 677 - 757.", "Norman, A. M. (1864) On undescribed British Hydrozoa, Actinozoa, and Polyzoa. Annals and Magazine of Natural History, series 3, 13, 82 - 90.", "Marques A. C., & Vervoort, W. (1999) Eudendrium arbuscula Wright, 1859 (Cnidaria, Hydrozoa): proposed conservation of the specific name. Bulletin of Zoological Nomenclature, 56, 16 - 18.", "Kramp, P. L. (1935 b) Polypdyr (Coelenterata) I. Ferskvandspolypper og goplepolypper. Danmarks Fauna, 41, 1 - 207.", "Christiansen, B. O. (1972) The hydroid fauna of the Oslo Fiord in Norway. Norwegian Journal of Zoology, 20, 279 - 310.", "Calder, D. R. (1972) Some athecate hydroids from the shelf waters of northern Canada. Journal of the Fisheries Research Board of Canada, 29, 217 - 228."]}